The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4102/sajip.v35i1.754
|View full text |Cite
|
Sign up to set email alerts
|

The survey of perceived organisational support: Which measure should we use?

Abstract: The psychometric properties of the original 36-item Survey of Perceived Organisational Support (SPOS) was examined along with a variety of shorter versions currently in use (16 items, eight items and three items). Factor analysis of the original SPOS measure is supportive of the original fi nding that the SPOS is unidimensional. Correlations among factor scores and SPOS scale scores suggest that either the eight-item or 16-item version would be just as effective as the 36-item version but even more effi cient.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
1
32
0
2
Order By: Relevance
“…Respondents indicated their level of agreement using 5-point Likert-type scale (1= strongly disagree, 5 = strongly agree). Worley et al (2009) verified the validity of this scale, and the Turkish translation was justified by Selçuk (2003).…”
Section: Methodsmentioning
confidence: 64%
“…Respondents indicated their level of agreement using 5-point Likert-type scale (1= strongly disagree, 5 = strongly agree). Worley et al (2009) verified the validity of this scale, and the Turkish translation was justified by Selçuk (2003).…”
Section: Methodsmentioning
confidence: 64%
“…Perceived organizational support is measured with 9 items scale of Survey of Perceived organizational support SPOSshort version which was developed by (Eisenberger, et al, 1986), The scale is a very well established measure and it has been used in many studies. The short version, research findings have found it more effective than the longer version (Worley, Fuqua & Hellman, 2009). POS is chosen to be one of the best predictors of Organizational Commitment and Employee behavior (Shore & Wayne, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…POS since its third decades ago, continues to contribute as a prominent concept and scale in understanding organizational behavior and it has been used specifically to understand the process of organizational commitment (Worley, Fuqua & Hellman, 2009). POS is defined as "Valuation of employee's contribution and care about employees' well-being" (Rhoades &Eisenberger, 2002).…”
Section: Perceived Organization Supportmentioning
confidence: 99%
“…Namun penghasilan dua komponen ini ternyata berbeza dengan kajian Eisenberger et al (1986) yang mencadangkan ukuran ini berbentuk unidimensi. Penelitian lanjut bagaimanapun mendapati pengasingan item-item ini sebenarnya tidak mempunyai makna konseptual yang jelas untuk diinterpretasikan (Worley, Fuqua & Hellman 2009). Pengasingan didapati berpunca daripada frasa item iaitu sama ada kenyataan positif atau negatif dan bukannya berdasarkan kandungan item (Benson & Hocevar 1985).…”
Section: Analisis Dataunclassified
“…Penghasilan dua faktor tidak semestinya menunjukkan kewujudan dua konstruk berbeza terutamanya apabila melibatkan pengelompokan dua item yang memiliki ciri-ciri bertentangan misalnya positif dan negatif (Spector et al 1997). Selaras dengan Eisenberger et al (1986) dan Worley et al (2009) Akhirnya, keputusan PCA ke atas ukuran PKBO juga menunjukkan menunjukkan hanya satu komponen terhasil dengan nilai eigenvalue melebihi 1, dan nilai varians diterangkan berjumlah 70.74%. Nilai pemberat faktor bagi setiap item adalah melebihi .60.…”
Section: Analisis Dataunclassified